Analisis Spasial Kerentanan Banjir Berbasis Geospasial di DAS Marisa Kabupaten Gorontalo - Risman Jaya; Ahmad Syamsu Rijal S; Gifari Sesar Pratama; Hendra Hendra; Dewa Oka Suparwata; La Ode Juni Akbar (-, 2026)
Historically, flooding in the Marisa River Basin (DAS) has had a significant impact on residential and agricultural areas, but spatial studies to map flood vulnerability are still very limited in the Marisa watershed. This study aims to map and identify the level of flood vulnerability in the Marisa watershed. Geographic Information Systems (GIS) as a geospatial approach with a scoring method for the main parameters in identifying flood vulnerability. The novelty of the study lies in the use of geological data and soil types, rainfall and topography combined with land use data in the Marisa watershed to identify flood vulnerability. The results show that areas with a high level of vulnerability are dominated by flat slopes, with an affected residential area reaching 773.36 Ha and rice fields 2,150.80 Ha, especially in Tunggulo and Tenilo Villages. Extreme rainfall in the upstream area and changes in land use are among the triggers of flooding, while Hydromorphic Alluvial soil and Qpr lithology in the downstream area exacerbate inundation. Therefore, spatial planning of the Marisa Watershed needs to focus on controlling land conversion in floodplains and strengthening conservation functions in upstream area